2011
DOI: 10.1021/jp110062y
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Hole on an Adenine−Thymine Radical Cation in B-Form DNA in Water

Abstract: A quantum mechanics/molecular mechanics (QM/MM) molecular dynamics (MD) simulation has been carried out using CP2K for a hole introduced into a B-form DNA molecule consisting of 10 adenine-thymine (A/T) pairs in water. At the beginning of the simulation, the hole wave function is extended over several adenines. Within 20-25 fs, the hole wave function contracts so that it is localized on a single A. At 300 K, it stays on this A for the length of the simulation, several hundred fs, with the wave function little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…It was found that immediately upon introduction of the hole its wavefunction is spread over 5 adenines, the length of the QM region in this simulation [8,9]. Within 20 fs, however, the hole is localized on a single one of these adenines [8,10]. It was shown that the contraction of the hole, that we have called self-trapping, is due to the polarization set up by the hole in the surrounding water [10,11].…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It was found that immediately upon introduction of the hole its wavefunction is spread over 5 adenines, the length of the QM region in this simulation [8,9]. Within 20 fs, however, the hole is localized on a single one of these adenines [8,10]. It was shown that the contraction of the hole, that we have called self-trapping, is due to the polarization set up by the hole in the surrounding water [10,11].…”
mentioning
confidence: 72%
“…Within 20 fs, however, the hole is localized on a single one of these adenines [8,10]. It was shown that the contraction of the hole, that we have called self-trapping, is due to the polarization set up by the hole in the surrounding water [10,11]. That this can happen on a fs time scale can be attributed to the librational motion of the water molecules [10].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Geometric conformation, which is sensitive to various factors such as temperature, solvent, and counter ions, affects the electronic coupling that alters the CT rate. 56,57 They also reported that polar surroundings suppress charge delocalization in DNA and the charge in GC repeats localizes on individual G's. 35 Conwell et al suggested the formation of a large polaron that spreads in length over 56 base pairs in their earlier work, 40,56 although they recently reported the localization of the charge on a single A in an A/T consecutive sequence due to the polarization of the surrounding water by the charge.…”
Section: ¹1mentioning
confidence: 98%
“…35 Conwell et al suggested the formation of a large polaron that spreads in length over 56 base pairs in their earlier work, 40,56 although they recently reported the localization of the charge on a single A in an A/T consecutive sequence due to the polarization of the surrounding water by the charge. 57 They also proposed that interstranded CT would not occur in such GC repeats and the polaron wave function is predominantly for the CT in DNA. 40 On the other hand, Sugiyama and Saito demonstrated stabilization of the charge over a couple of G's based on theoretical calculations.…”
Section: ¹1mentioning
confidence: 99%